PROFIT SHARING SYSTEM AND LOSS BURDEN IN CATTLE REARING SHARIA ECONOMIC LAW PERSPECTIVE (Study in Sriwaylangsep Village, Kalirejo District, Central Lampung Regency) - Yanuar Saputri; Khoiruddin; Gatot Bintoro Putro Aji (PT. Radja Intercontinental Publishing, 2026)
This study aims to analyze the way of profit sharing and loss responsibility in cattle farming in Sriwaylangsep Village, Kalirejo District, Central Lampung Regency, and review it from the perspective of Sharia Economic Law. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The focus of this research is on the implementation of mudharabah contracts between capital owners and managers in cattle farming activities. The results of the study show that the cooperation carried out by the community in general has adopted the concept of mudharabah with a profit-sharing system. However, in its implementation there are still inconsistencies with sharia principles, especially in the distribution of profits that are not always in accordance with the initial agreement. In addition, the mechanism for liability for losses has also not been implemented optimally, and there are weaknesses in the aspect of transparency due to the absence of a written contract. Judging from Sharia Economic Law, this practice has not fully fulfilled the principles of justice ('adl), usefulness (maslahah), partnership (shirkah), and transparency and accountability. Therefore, improvements are needed through the creation of a written contract, clarity of the distribution of results, and strengthening the agreement between the parties to avoid the element of gharar. Thus, it is hoped that the mudharabah practice applied can run fairly, transparently, and in accordance with sharia provisions.